Stress factors and coping strategies of parents with children treated by hemodialysis: A qualitative study - (:unkn) unknown (W.B. Saunders, 2002)
The purpose of this study was to describe the common stress factors and coping strategies of parents whose children had been treated by hemodialysis. This study was conducted by using focus group interviews. The sample was composed of 31 parents. Five focus groups were made up from these parents. Data were analyzed by using the manifest content analysis method. According to the results, common stress factors of parents included financial and bureaucratic problems, growth and development of ill children, fluid-diet restriction and educational problems of children, lack of social support, and anxiety about losing their children at any moment. Coping strategies of parents were to give their attention to the positive side of matters, to share their feelings with their spouse or other parents, to cry, or pray. Copyright 2002, Elsevier Science (USA). All rights reserved.